Structure of two human alpha-tubulin genes. - Wilde, C D (1982)
The ability of a chicken alpha-tubulin cDNA probe to cross-hybridize with human DNA under stringent conditions has been exploited to screen two independently constructed human genomic libraries. Nine clones were isolated, accounting for 60% of the bands observed in a whole genomic Southern blot of human DNA. Two clones were selected for further analysis by restriction mapping, orientation experiments using 3'- or 5'-specific probes, and electron microscopy of heteroduplexes. One clone, 2 alpha, contains an alpha-tubulin-specific region of 5.0 kilobases that includes three intervening sequences. The second clone, 19 alpha, contains an alpha-tubulin-specific region of 5.4 kilobases and has somewhat diverged 5' and 3' ends. Clone 19 alpha has only two intervening sequences that correspond to the first two in clone 2 alpha. However, these intervening sequences differ in size between clones 2 alpha and 19 alpha and show no detectable sequence homology. The sum of the lengths of sequences in either clone that hybridize to the cDNA probe accounts for essentially the entire length of the cDNA molecule.